HUBUNGAN KEPERDATAAN ANAK LUAR NIKAH AKIBAT PERCERAIAN LIâAN MENURUT KOMPILASI HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Mayangsari, Endah; Hanifah, Mardalena; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Compilation of Islamic Law explains that children from the extramarital relationships have only civil relationship with her mother. Such conditions that, in contradiction with the Act No. 35 of 2014 regarding Child Protection which regulates the rights of children on welfare by her parents not the mother alone. The concept of Islamic law (Fiqh), a child outside marriage (zina) is the responsibility of the mother to just have a civil relationship to her mother alone, so that legally fall his obligation to provide a living, heritage and be the guardian of the child. In practice proceedings, the authors see their case Jinhuang and denial of children on the register No. 163 K / AG / 2011 in the Supreme Court is able to answer the question of the protection of children out of wedlock, while maintaining the mandate of the Act No. 35 of 2014 on Protection of Children and Islamic Law Compilation.The method used is Library Research with normative juridical approach, while the nature of this thesis research is exploratory (exploratory or browsing). How research is to conduct a literature study by visiting and looking for reference books related to several libraries. Results of the study found was the order for the achievement of the rights of a child out of wedlock as a result of divorce Jinhuang called the child of adultery, the wife who has been in the Jinhuang can attest to the Religious Court that the man is the biological father of her child and the wife was able to submit a new application to the Religious Court in terms of ratification of the child. Advice writer, is expected to the wife / woman must not approach fornication. Zina in view are forbidden in Islamic law and national law because there are parties who do not now in view of the public eye because of deeds done.